2020
DOI: 10.1186/s12889-020-09438-2
|View full text |Cite
|
Sign up to set email alerts
|

Can complex programs be sustained? A mixed methods sustainability evaluation of a national infant and young child feeding program in Bangladesh and Vietnam

Abstract: Background: Poor early-life nutrition is a major barrier to good health and cognitive development, and is a global health priority. Alive & Thrive (A&T) was a multi-pronged initiative to improve infant and young child feeding behaviors. It aimed to achieve at-scale child health and nutrition improvements via a comprehensive approach that included nutrition counseling by health workers, policy change, social mobilization and mass media activities. This study evaluated the sustainability of activities introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 56 publications
(90 reference statements)
1
24
0
Order By: Relevance
“…Improving complementary feeding is particularly challenging globally because of the multiple complex behaviors involved [ 38 ]. Previous study showed that training, monitoring, and evaluation declined in frequency and quality, or were eliminate altogether which influenced the Sustainability of the Alive & Thrive initiative (A&T) in Bangladesh and Vietnam [ 39 ], which was in accordance with our findings. Regular monitoring along with process and impact evaluations feed information back to programs is necessary [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…Improving complementary feeding is particularly challenging globally because of the multiple complex behaviors involved [ 38 ]. Previous study showed that training, monitoring, and evaluation declined in frequency and quality, or were eliminate altogether which influenced the Sustainability of the Alive & Thrive initiative (A&T) in Bangladesh and Vietnam [ 39 ], which was in accordance with our findings. Regular monitoring along with process and impact evaluations feed information back to programs is necessary [ 38 ].…”
Section: Discussionsupporting
confidence: 92%
“…When A&T ended in December 2014, project support ceased for IYCF-specific financial incentives, refresher trainings, or job aids, although BRAC still expected IYCF counseling and education services to continue. While some A&T program activities and benefits continued, other activities, such as training and reporting, ceased altogether or experienced a substantial attenuation in implementation [51]. For example, 2 years after A&T ended, exposure to volunteer CHWs for interpersonal counseling was higher in intensive intervention areas than comparison areas; however, it had still experienced a decrease from 87.4% to 59.3% in intervention areas [44].…”
Section: Study Context: Alive and Thrive Initiative In Bangladeshmentioning
confidence: 99%
“…As part of a larger effort to assess the sustainability of A&T in Bangladesh, focus groups were conducted with representatives from multiple sub-districts in which A&T was implemented [51]. Seven districts were purposively selected to achieve geographic variability from a sample of 10 districts that had participated in a previous A&T endline evaluation.…”
Section: Study Sample and Data Collectionmentioning
confidence: 99%
“…The issues of sustainability are becoming increasingly important in implementation science and are of interest among researchers, implementers, donors and stakeholders who wish to improve the sustainability of effective public health programmes (32)(33)(34)(35) . Previous literature suggests considering sustainability in implementation science frameworks as a theory-driven approach to guide the design, development, implementation, evaluation and sustainability of interventions (36) .…”
Section: Sustainability Of the Brac Home-fortification Programmementioning
confidence: 99%